THE INTERFERENCE OF NATIVE LANGUAGE INTO ENGLISH PRONUNCIATION - Taufik Suadiyatno (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2015)
This research was aimed at finding out how the native language interfere the English pronunciation and to identify the native language sounds that interfere the English pronunciation of the third semester of English Department students of IKIP Mataram in the academic year 2013/2014. This research was a qualitative research. The subjects of this research were the third semester of English Department students of IKIP Mataram in the academic year 2013/2014 that were selected based on certain category. The data was collected through observation and analyzed through some steps namely (1) transcribing the data, (2) reducing the data, (3) displaying the data that have been reduced and then drawing and verifying conclusion. Based on the result of data analysis it can be concluded that the native language interfere the studentsâ€™ English pronunciation automatically when the English words sounds that they produced do not exist in their mother tongue. The researcher found some native language sound that interfere their English pronunciation, such as:Â  vowel sound: /E/ for /Ã/, /a/ for /É‘Ã‰/, /I/ for /iÃ‰/, /Â«/ for /Ã¤Ã‰/, /U/ for /uÃ‰/, /a/ and /Â«/, for /É‘/. Where as in consonant are: /p/ for /f/, /t/ for /T/ and /D/, and /s/ for /Êƒ/.